Impact of training and development and employee engagement on employee performance among medium manufacturing enterprises (Global Business Management Review (GBMR), 2023)
This study's overarching goal is to empirically examine how training and development impact employee performance in Malaysia's medium-sized manufacturing enterprises (MMEs). A comprehensive questionnaire is used to collect the data from 280 employees of MMEs. This study conducted a cross-sectional survey, and the data were analyzed using SmartPLS 3.3.9 for multivariate statistical analysis. The partial least square structural equation modeling (PLS-SEM) method determines the relationship between exogenous and endogenous variables. The development of an integrated research framework was accomplished. According to the study's findings, training and development affect employee performance. The research was conducted in MMEs, and the analysis is based on cross-sectional data that cannot be contextualized for a broader range of industries. The study results will assist policymakers, legislators, and MME management in lobbying for practical and well-articulated training and development strategies to improve employee engagement and performance. This study contributes to the body of knowledge by providing empirical evidence that training and development influence employee performance in Malaysian MMEs by combining essential parts of existing literature.